Pinheiro-Machado, Rosana. Counterfeit Itineraries in the Global South: The human consequences of piracy in China and Brazil - Piza, Douglas de Toledo (Tempo Social, 2018)
Book Review: Counterfeit Itineraries in the Global South: The human consequences of piracy in China and Brazil, London and New York, Routledge, 2017, by Rosana Pinheiro-Machado